2022
DOI: 10.1002/smm2.1102
|View full text |Cite
|
Sign up to set email alerts
|

2D π‐conjugated metal–organic frameworks for CO2 electroreduction

Abstract: Electrochemically converting CO2 molecules into valuable chemicals and fuels opens up a promising route to utilize CO2 source. To overcome the low efficiency and durability that hinder its practical applications, tremendous research efforts have been devoted to nano‐level or atomic‐level catalyst design. The advent of metal–organic frameworks (MOFs) provides novel opportunities for CO2 reduction catalysts, which may integrate the respective advantages of traditional catalysts and single‐atom catalysts. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…First, Fe SAS/Tr-COF photocatalysts with atomically dispersed Fe atoms can expose abundant metal active sites to effectively capture CO 2 molecules. Second, the formed Fe–N charge bridge in Fe SAS/Tr-COFs can provide an additional channel for further ultra-fast electron migration from Tr-COF units to atomically dispersed Fe centers, thus achieving the long-life carrier separation. , Third, the absorbed CO 2 could be effectively reduced to the CO product on the Fe SAS/Tr-COF catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…First, Fe SAS/Tr-COF photocatalysts with atomically dispersed Fe atoms can expose abundant metal active sites to effectively capture CO 2 molecules. Second, the formed Fe–N charge bridge in Fe SAS/Tr-COFs can provide an additional channel for further ultra-fast electron migration from Tr-COF units to atomically dispersed Fe centers, thus achieving the long-life carrier separation. , Third, the absorbed CO 2 could be effectively reduced to the CO product on the Fe SAS/Tr-COF catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In the past several decades, many categories of MOFs have been successfully synthesized using different metal precursors and various kinds of organic ligands/linkers. ,, Though most MOF catalysts tend to facilitate C 1 production in electrochemical CO 2 RR, great progresses have also been achieved in the efficient CO 2 conversion toward C 2+ products with pristine MOFs. , Previous studies also found that some kinds of MOFs, such as porphyrin/phthalocyanine-based MOFs and trimesic acid-constructed Cu–MOFs (denoted as HKUST-1), show a huge potential of promoting C 2+ generation in the electrocatalytic CO 2 RR. , In this section, recent advances in the electrocatalytic CO 2 RR on pristine MOFs toward C 2+ products will be systematically introduced based on the types of organic ligands used to construct MOFs. Table summarizes the CO 2 RR performance of typical pristine MOFs toward C 2+ products.…”
Section: Pristine Mof For Electrocatalytic Co2rrmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), as a unique type of porous materials, are typically constructed from metal nodes and organic ligands/linkers. Because of the ultrahigh surface area, structural diversity, and chemical tunability, MOFs have drawn considerable attention in various applications, including gas adsorption and separation, , catalysis, magnetism, , chemical sensing, and biomedicine. In particular, MOFs have also shown promising applications in the electrochemical CO 2 RR as a result of the following advantages. First of all, the porous structure of MOFs can promote the CO 2 adsorption/activation and shorten the transport distance between CO 2 molecules and metal active sites. , Second, metal clusters in MOFs contribute to enhancing the catalytic activity and turnover frequency. , Third, the atomic-level periodicity of metal nodes in MOF structures endows the precise control of metal active sites for electrocatalysis. , Fourthly, perturbation of coordination microenvironment of metal centers can affect the charge density distribution of catalytic active sites, making it possible to delicately regulate the adsorption and/or desorption energy of various key reaction intermediates. Fifthly, modification of organic ligands with various functional groups can adjust the free energy of different critical intermediates that are adsorbed on catalytic active sites. , Last but not the least, the well-defined and tunable crystallographic structure of MOFs is conducive to build theoretical calculation models to study the structure–activity relationship. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…The continuously excessive release of greenhouse gas, CO 2 , has caused serious global climate warming and environmental degradation. In this regard, the emerging sequestration [1], chemical fixation [2], and electro/photo/thermochemical reduction technologies [3][4][5][6][7][8][9] have been developed to alleviate CO 2 emissions. The electrochemical CO 2 reduction reaction (CO 2 RR) to yield high-value-added fuels and chemicals provides a promising approach towards an sustainable carbon-cycle utilization, especially when powered by renewable energy resources [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%